2018
DOI: 10.1002/aoc.4377
|View full text |Cite
|
Sign up to set email alerts
|

Palladium complexes of bidentate pyridine N‐heterocyclic carbenes: Optical resolution, antimicrobial and cytotoxicity studies

Abstract: A series of bidentate pyridine‐functionalized palladium N‐heterocyclic carbene (Pd NHC) complexes with various wingtip substituents (R = methyl, phenyl and tert‐butyl) have been synthesized and evaluated for their potential biomedical applications as antimicrobials and antiproliferative drug candidates. The obtained Pd NHC complexes were applied in a standard broth microdilution assay for determination of their antimicrobial activities against thirteen strains of pathogenic microorganisms. In addition to that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 79 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Specific examples of metallo-complexes demonstrating antimicrobial activity include N-heterocyclic carbene (NHS) complexes of silver and gold, auranofin (a clinically approved antirheumatic drug), colloidal bismuth citrate (CBS, a clinically approved antiulcer drug), and gallium nitrate. On the other hand, although palladium remains less explored in this context, there appears to be growing interest, with a steady number of studies published over the years [14][15][16][17][18][19][20]. Palladium palladacycles have historically garnered attention as anticancer agents due to their potential for diverse coordination geometry and cognate anticancer mechanisms distinct from those of platinum-based therapies such as cis-platin [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific examples of metallo-complexes demonstrating antimicrobial activity include N-heterocyclic carbene (NHS) complexes of silver and gold, auranofin (a clinically approved antirheumatic drug), colloidal bismuth citrate (CBS, a clinically approved antiulcer drug), and gallium nitrate. On the other hand, although palladium remains less explored in this context, there appears to be growing interest, with a steady number of studies published over the years [14][15][16][17][18][19][20]. Palladium palladacycles have historically garnered attention as anticancer agents due to their potential for diverse coordination geometry and cognate anticancer mechanisms distinct from those of platinum-based therapies such as cis-platin [20].…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that bacterial susceptibility to chemotherapeutic metallo-complexes is significantly influenced by the nature of the coordinated metal ion and its associated coordination sphere. Indeed, in most of the aforementioned studies [14][15][16][17][18][19][20][21], it was found that palladium-derived complexes exhibited significantly higher antibacterial and antifungal activity compared to the corresponding free organic ligands.…”
Section: Introductionmentioning
confidence: 99%